Latest advances and future perspectives in Armillaria research. Issue 1 (2nd January 2019) - Heinzelmann, Renate; Dutech, Cyril; Tsykun, Tetyana; Labbé, Frédéric; Soularue, Jean-Paul; Prospero, Simone
Abstract: The basidiomycete genus Armillaria s.l. ( Armillaria s.s. and Desarmillaria ) has a worldwide distribution and plays a central role in the dynamics of numerous woody ecosystems, including natural forests, tree plantations for timber production, orchards, vineyards and gardens. Early studies have shown that all Armillaria species are capable of degrading dead woody substrates, causing white rot. Moreover, most species exhibit a parasitic ability, and can be considered as facultative necrotrophs. Although over the years extensive research has been conducted on the phylogeny, biology and ecology of different Armillaria species, numerous theoretical and applied questions remain open. Recently published studies have provided new perspectives, the most significant of which we present in this review. First, new investigations have highlighted the importance of a multilocus approach for depicting the phylogeny of the genus Armillaria . Second, the importance of clonality and sexuality for the different species is now better described, enabling a more accurate prediction of population dynamics in various environments. Third, genome sequencing has provided new insights into genome evolution and the genetic basis of pathogenicity and wood degradation ability. Fourth, several new studies have pointed out the possible influence of climate change on Armillaria distribution, biology and ecology, raising questions regarding the future evolution of Armillaria species and their effect on ecosystems. In this review, we also give a state-of-the-art overview of the control possibilities of parasitic Armillaria species. Finally, we outline some still open questions in Armillaria research, the investigation of which will strongly benefit from recent methodological advances.